Medical Humanities at the University of Wales Swansea. Issue 1 (1st June 2001) - Evans, Martyn; Greaves, David
Abstract : The UK's first taught master's degree in medical humanities involves a field of inquiry that is frequently philosophical, pursuing interests and questions traditionally arising in medical philosophy and ethics, but on a larger interdisciplinary canvas, drawing upon literature and the visual arts, sociology and anthropology, social history and politics, and theological and religious perspectives.